Ocena aktywności żerowej "cervus elaphus" na zrewitalizowanych łąkach śródleśnych na podstawie analizy intensywności zgryzania runi = Evaluation of "cervus elaphus" foraging activity on revitalised mid-forest meadows based on analysis of sward browsing intensity - Daszkiewicz, Jędrzej; Goliński, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Aim of this study is evaluation of red deer foraging activity on renovated mid-forest meadows using different methods. Research, carried out on experimental sites, showed, that most of grazing activity of animals falls on areas renovated by full tillage method combined with sowing of specialised seed mixtures.
Keywords: jeleń europejski; łąki śródleśne; renowacja runi; aktywność żerowa; intensywność zgryzania runi; red deer; mid-forest meadows; sward renovation; foraging activity; sward browsing intensity